Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship